2012
DOI: 10.1002/cctc.201200460
|View full text |Cite
|
Sign up to set email alerts
|

NanoSelect Pd Catalysts: What Causes the High Selectivity of These Supported Colloidal Catalysts in Alkyne Semi‐Hydrogenation?

Abstract: In recent years, many articles describing the preparation of supported colloidal catalysts have been published. The semi‐hydrogenation of alkynes to yield cis‐alkenes is often used as a test reaction in these publications. Many highly selective catalysts are described. However, a satisfactory explanation for the high reported selectivity has never been shown. Here we report a study on the possible effects that lead to the large selectivity differences between current commercial Pd/C catalysts and our newly dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
72
1
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 70 publications
(75 citation statements)
references
References 17 publications
1
72
1
1
Order By: Relevance
“…Interestingly, phosphorous appears to be mainly localised in the areas where Ru is also present, corroborating previous hypotheses that the ligand is bound to the metallic nanoparticle through phosphate heads and to the carrier through N-OH dispersion interactions. 31 This clear partition between the type of ligand adsorbed on the nanoparticles and that on the support enable, for the first time, the direct estimation of the ligand content per nanoparticle. Assuming an hcp unit cell with atomic packing of 0.76, 57 and considering the dispersion of Ru, we have first calculated the moles of surface Ru atoms.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Interestingly, phosphorous appears to be mainly localised in the areas where Ru is also present, corroborating previous hypotheses that the ligand is bound to the metallic nanoparticle through phosphate heads and to the carrier through N-OH dispersion interactions. 31 This clear partition between the type of ligand adsorbed on the nanoparticles and that on the support enable, for the first time, the direct estimation of the ligand content per nanoparticle. Assuming an hcp unit cell with atomic packing of 0.76, 57 and considering the dispersion of Ru, we have first calculated the moles of surface Ru atoms.…”
Section: Resultsmentioning
confidence: 93%
“…13,25,[38][39][40][41] Herein, we report the synthesis of Ru-HHDMA colloids displaying a narrow particle size distribution centred at 1.5 nm, and the subsequent deposition onto a TiSi 2 O 6 carrier. Characterisation by inductively coupled plasma optical emission spectroscopy, elemental analysis, scanning transmission electron microscopy, energy dispersive X-ray mapping, 31 P and 13 C magic angle spinning nuclear magnetic resonance, X-ray photoelectron spectroscopy, diffuse reflectance infrared spectroscopy, and temperature-programmed reduction with H 2 confirms the desired interaction of the ligand and the metal nanoparticle in the resulting catalyst. In order to explore the advantages of ligand modification in comparison with the state-of-the-art Ru/C material, the catalyst performance has been evaluated in the continuousflow three-phase hydrogenation of levulinic acid to -valerolactone in water at different temperatures, pressures, and flow rates.…”
Section: Introductionmentioning
confidence: 80%
See 1 more Smart Citation
“…Hume-Rothery nanophases, for example, Fe 4 Al 13 , [20] PdGa, [21] and NiGa, [22] attracted attention as selective semihydrogenation catalysts of alkynes to alkenes (active site isolation concept). These findings suggest inexpensive and abundant alternatives for established but rare and precious noble metal catalysts (for example, Pt, [23] Pd, [24] Ru, [25] Rh, [26] or Au [27] ). The insertion of a nitrile into the MÀH bonds of 1 leading to 2 in a clean reaction provides a first study case (molecular model) for surface reactions on hydrogenated Hume-Rothery type intermetallic nanophases showing cooperative interaction of A and B sites.…”
mentioning
confidence: 84%
“…An interesting feature of this reactioni s that both molecular and particle catalysts ystems are active. [45,50,51,[84][85][86][87][88][89] Our group has previouslyr eported ac atalytic system that was proposed to proceed via an in situ generated molecular [Pd 0 (IMes)] speciesa st he active catalyst( IMes = 1,3-bis-mesityl-imidazol-2-ylidene) (Scheme 5). [46,[90][91][92] Sprengers et al reported that the in situ generated catalyst is significantly more active than the isolated catalyst.…”
Section: Pdmentioning
confidence: 99%